Implementasi Pembelajaran Problem Based Learning Berbantuan Simulasi PhET pada Pelajaran Fisika - Pieter, Jan; Risamasu, Putu Victoria M (Journal of Health, Education, Economics, Science, and Technology (J-HEST), 2024)
The aim of this research was to determine the improvement in Physics learning outcomes and the effect of implementing the Problem Based Learning model assisted by PhET Simulation on students' mastery of concepts in the Physics of Elasticity and Hooke's Law material at high school level in Jayapura City. The research sample was taken using a purposive sampling method, obtained from class XI students. The evaluation test instrument is used to see students' mastery of concepts with 20 questions. Data analysis used N-Gain analysis and F test. From the results of data analysis, it was found that in the control class, the average N-Gain value was 0.63, which was categorized as medium, in the experimental class, the average N-Gain value was 0.73. high category. Furthermore, there is a significant influence between the Problem Based Learning model assisted by PhET simulation on students' learning interest and there is a significant influence between the Problem Based Learning model assisted by PhET simulation on student learning outcomes with a sig value of 0.002 < 0.05.